Bicyclic lactones from the octocoral Dendronephthya mucronata. Issue 7 (3rd April 2021) - Ngoc, Ninh Thi; Hanh, Tran Thi Hong; Nguyen, Hai Dang; Quang, Tran Hong; Cuong, Nguyen Xuan; Nam, Nguyen Hoai; Thung, Do Cong; Ngai, Nguyen Dang; Kiem, Phan Van; Minh, Chau Van
Abstract: The MeOH extract of the Vietnamese octocoral Dendronephthya mucronata afforded four bicyclic lactones (1 –4 ), including three new compounds namely dendronephthyones A–C (1 –3 ), after subjecting it on various chromatographic separations. The structures of the isolated compounds were established by spectroscopic experiments including 1D, 2D NMR, CD and HR-QTOF-MS. In addition, compounds 1 –4 were found to exhibit selective cytotoxicity against the HeLa human cancer cell line with IC50 values of 32.48 ± 2.15, 30.12 ± 1.86, 35.14 ± 1.57 and 14.45 ± 1.34 μM, respectively. Abstract :